mazEF Homologue Has a Minor Role in Staphylococcus epidermidis 1457 Virulence Potential - Gaio, Vânia; Lima, Tânia; Vilanova, Manuel; Cerca, Nuno; França, Angela (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus epidermidis biofilm cells are characterized by increased antimicrobial tolerance and improved ability to evade host immune system defenses. These features are, in part, due to the presence of viable but non-culturable (VBNC) cells. A previous study identified genes potentially involved in VBNC cells formation in S. epidermidis biofilms, among which SERP1682/1681 raised special interest due to their putative role as a toxin-antitoxin system of the mazEF family. Herein, we constructed an S. epidermidis mutant lacking the mazEF genes homologues and determined their role on (i) VBNC state induction during biofilm formation, (ii) antimicrobial susceptibility, (iii) survival in human blood and plasma and (iv) activation of immune cells. Our results revealed that mazEF homologue did not affect the proportion of VBNC cells in S. epidermidis 1457, refuting the previous hypothesis that mazEF homologue could be linked with the emergence of VBNC cells in S. epidermidis biofilms. Additionally, mazEF homologue did not seem to influence key virulence factors on this strain, since its deletion did not significantly affect the mutant biofilm formation capacity, antimicrobial tolerance or the response by immune cells. Surprisingly, our data suggest that mazEF does not behave as a toxin-antitoxin system in S. epidermidis strain 1457, since no decrease in the viability and culturability of bacteria was found when only the mazF toxin homologue was being expressed.